B-doped hardystonite bioceramics from preceramic polymers and fillers: Synthesis and application to foams and 3D-printed scaffolds. Issue 4 (April 2017) - Elsayed, Hamada; Sinico, Mirko; Secco, Michele; Zorzi, Federico; Colombo, Paolo; Bernardo, Enrico
Abstract: Highly porous hardystonite-based bioceramics, in the form of foams and 3D scaffolds, were obtained by the thermal treatment, in air, of silicone resins and engineered micro-sized oxide fillers. Besides CaO and ZnO precursors (CaCO3 and ZnO powders), calcium borate, in both hydrated and anhydrous form (Ca2 B6 O11 ·5H2 O and Ca2 B6 O11, respectively), was added to commercial silicone resins, with a significant impact on the microstructural evolution. In hydrated form, calcium borate led to a substantial foaming of silicone-based mixtures, at low temperature (420 °C); after dehydration, upon firing, the salt provided a liquid phase, favouring ionic interdiffusion, with the development of novel B-contaning hardystonite-based solid solutions (Ca2 Zn1-x B2x Si2-x O7 ). Although fired at lower temperature than previously developed silicone-derived hardystonite cellular ceramics (950 °C, instead of 1200 °C), the newly obtained foams and scaffold exhibit substantial improvements in the mechanical properties.